ANALISIS PENERAPAN KURIKULUM 2013 DI TK NEGERI PEMBINA 3 PEKANBARU - Nurhayati '; Daviq Chairilsyah; Febrialisma ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the planning, organizing, implementation and evaluation or assessment of the implementation of curriculum, 2013 in TK Negeri Pembina 3 Pekanbaru. The method used in this research is descriptive qualitative method, a method that is aimed to define or explain what their research results. That is the subject of this research is the first person the principal and two teachers at TK Negeri Pembina 3 Pekanbaru. Collecting data this study uses three main techniques were interviews, observation and documentation. Based on data analysis and discussion that has been done can disumpulkan kindergarten curriculum planning, 2013 in Negeri Pembina 3 Pekanbaru is appropriate to run well. On indicators of planning managers have implemented the curriculum, the curriculum used curriculum 2013. Organizing the curriculum in 2013 from the already excellent infrastructure. On the organizational structure of TK Negeri Pembina 3 Pekanbaru own organizational structure starting from the chairman, treasurer, secretary, manager, teacher. It looks at the observations and the results of wawanaca own duties and responsibilities of each. On performance indicators TK Negeri Pembina 3 Pekanbaru has had and apply some guidebooks implementation, books administration and management information systems in kindergarten. In the evaluation indicators TK Negeri Pembina 3 Pekanbaru has implemented several ratings are cognitive, affective and psychomotor. Keywords: Implementation of the curriculum in 2013.